Asas Kepastian Hukum dalam Penyelengaraan Perpajakan di Indonesia - Iyan Nasriyan (Universitas Kuningan, 2019)
Law is a regulation made by an authorized institution to regulate public order. A realistic approach to law is legal certainty. The purpose of this research is to find out the principle of legal certainty that plays a role in the administration of taxation in Indonesia. The research method used by the author is Normative Juridical, with data collection tools through literature study. The results showed that legal certainty is